Capitalism Its Origins and Evolution as a System of Governance - Scott, Bruce R.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Two systems of governance, capitalism and democracy, prevail in the world today. Operating in partly overlapping domains, these systems influence and transform each other, but the nature of this interaction is often misunderstood -- largely because capitalism has not been recognized as a system of governance. Rejecting the simple definition "capitalism = actions of firms in markets," Harvard's Bruce R. Scott offers instead a conception of capitalism as a three-level system akin to organized sports, in which games (markets) are conducted according to rules administered by referees (regulators), which in turn are shaped and directed by sports' governing bodies (political authorities). Tracing the evolution of capitalism from a variety of perspectives, Scott shows how governance has always been key to the system. Historically, capitalism was not a natural outgrowth of trade; it could not have emerged without political authorization for the creation of markets for land, labor, and capital. Urgently needing funds for military defense, regimes ceded some power to a new class of economic actors, spelling out their rights and responsibilities with corporate charters. The United States Constitution was anomalous in reserving to individual states the power to grant such charters, with the result that states compete to offer firms the least regulation. The Constitution also gave exceptional powers to the Supreme Court, which has interpreted the Constitution as mandating laissez-faire policies. It is impossible to adequately understand capitalism without understanding the role played by governance. This book challenges the notion of a "universal" model of capitalism, particularly one based on the US system, and illuminates the broader frameworks upon which markets depend.
The Globalization of Markets and the Resilience of Capitalist Democracies: Observable Trends and Explanatory Theory: Globalization and Income Convergence -- The Political Economy of Capitalism -- Capitalism, Democracy and Inequality. Creating Capitalism, with or Without Democracy: Creating Capitalism in Europe -- Creating Capitalism and Democracy in the United States: The Symbiosis of Two Systems of Governance (1630-1830) -- Creating Capitalism in Latin America. Barriers to Development in Capitalist Democracies: One Country-Two Systems: The Case of Italy- One Country - Two Systems: The United States (1878-1970) -- Capitalism and Democracy in the US (1830-1930): Antagonistic Symbiosis. Catch-Up Strategies Post-World War II: Import Substitution -- Neo-Mercantilism -- The Washington Consensus. "Antagonistic Symbiosis" in a Contemporary Context: Latin American Reform and Instability -- Capitalism and Democracy in the US (1970-2006): Liberalization and Inequality -- Conclusions -- Implications.
Keywords: Economics; History; Development Economics; Endogenous growth (Economics).; Economics/Management Science; Development Economics; History; Economic Systems; Economic Growth; Political Science, general